Study on the Chemical Constituents of Essential Oils from the Leaves of Viscum ovalifolium and Loranthus pentapetalus Roxb. Parasitizing on Guaiacum spp. - Chen, Rui; Huo, Lini; Liao, Yanfang; Yuan Li, Pei; Lu, Rumei; Zhang, Hongyi (Asian Journal of Chemistry, 2012)
The chemical composition of the essential oils obtained from the leaves of Viscum ovalifolium and Loranthus pentapetalus Roxb. parasitizing on Guaiacum spp. were examined by GC-MS analysis. Fourty seven compounds were isolated and 20 compounds were identified in the V. ovalifolium that composed about 72.91 % of the total essential oils. Besides, 42 compounds were isolated and 33 compounds were identified in the L. pentapetalus that composed about 87.88 % of the total essential oils. There were 12 same constituents in these two samples and the main constitutes of them were phytol, phytone, 1,3-dichloro-benzene and dibutyl phthalate, etc., which might be related to their host.